Carbon Dots from Coffee Grounds: Synthesis, Characterization, and Detection of Noxious Nitroanilines - Alexandra I. Costa; Patrícia D. Barata; Bianca Moraes; José V. Prata (Chemosensors, 2022)
Coffee ground (CG) waste is generated in huge amounts all over the world, constituting a serious environmental issue owing to its low biodegradability. Therefore, processes that simultaneously aim for its valorization while reducing its environmental impact are in great demand. In the current approach, blue luminescent carbon dots (C-dots) were produced in good chemical yields from CGs following hydrothermal carbonization methods under an extended set of reaction parameters. The remarkable fluorescent properties of the synthesized C-dots (quantum yields up to 0.18) allied to their excellent water dispersibility and photostability prompted their use for the first time as sensing elements for detection of noxious nitroanilines (NAs) in aqueous media. Very high levels of NA detection were achieved (e.g., limit of detection of 68 ppb for p-nitroaniline), being the regioisomeric selectivity attributed to its higher hyperpolarizability and dipole moment. Through ground–state and time-resolved fluorescence assays, a static fluorescence quenching mechanism was established. 1H NMR titration data also strongly suggested the formation of ground–state complexes between C-dots and NAs.